Inkjet-printed quantum dot-based sensor for structural health monitoring. Issue 1788 (2015) - Hartwig, Melinda; Ortlepp, Franz; Möbius, Martin; Martin, Jörg; Otto, Thomas; Geßner, Thomas; Baumann, Reinhard R.
ABSTRACT: A sensor which detects mechanical stresses and stores the position and the strength of these loads by color change of embedded quantum dots (QDs) is presented. The top and bottom electrodes of the sensor are inkjet-printed which leads to a fast and accurate deposition of thin (approx. 50 - 300 nm) and conductive layers. The used silver and poly(3, 4-ethylenedioxythio-phene) polystyrene sulfonate (PEDOT:PSS) inks are optimized in terms of printability and opportunities of functionality forming without influencing the active layer of the sensor. The active layer of the sensor is spin-coated and consists of the QDs embedded in semi-conducting poly(9-vinylcarba-zole) (PVK). The hole transport characteristic of PVK and the band level alignment of the used materials ensures the preferred injection of only one type of charge carrier into the QDs. As a result the mechanical stress is visualized by a decreasing in photoluminescence (PL) of the QDs.